Impact of Growth Mindset-Enhanced Trauma Education on Criminal Legal Professionals’ Attitudes and Perceptions - Mckinsey, Eva (Criminal justice and behavior, 2023)
Addressing mass incarceration in the United States will require criminal legal professionals to shift away from carceral punishment and toward alternative approaches to justice. Education on the physiological, social, and behavioral impacts of traumatic events (i.e., trauma education), especially when enhanced with messaging about the malleability of behavior (i.e., growth mindset intervention), may help promote this shift. We assessed the impact of trauma education alone and enhanced with a growth mindset intervention on 344 U.S.-based criminal legal professionals’ attitudes about the criminal legal system and perceptions of trauma-informed judicial practice, and assessed whether profession type moderated intervention impact. Compared with trauma education alone, mindset-enhanced trauma education led to increased perceived appropriateness of considering trauma in judicial decision-making (main effect) and greater support of alternative sentencing for nonviolent crimes among lawyers and judges (moderation effect). Although effects were small, findings support the enhancement of trauma education with growth mindset interventions.